Neither Jew nor Greek Ignatius of Antioch’s Use of Scripture and the “Parting(s) of the Ways” - Sargent, Benjamin (2023)
Ignatius of Antioch makes very little reference to specific texts from the Scriptures of Israel. This has been interpreted as evidence of little interest in Scripture, which, in turn has been used to plot Ignatius on a parting of the ways trajectory. The evidence for this interpretation is weak. Ignatius refers to Scripture in a way that is comparable to some Pauline letters. Furthermore, his statements about Scripture and his use of texts suggest that he differs little from the hermeneutical assumptions of apostolic Christianity.
Keywords: Scripture; Interpretation; Christian Origins; parting of the ways; Apostolic Fathers; Ignatius of Antioch